EFL Teachers’ ICT Literacy Acquisition to Online Instruction during COVID-19 - Kanchai, Thebporn (LEARN Journal: Language Education and Acquisition Research Network, 2021)
Due to the global COVID-19 pandemic, educational systems, including teaching a foreign language, have been interrupted and classroom-based teaching paradigms have rapidly shifted to online platforms. Despite the emphasis of technology in language education, Thai tertiary educators are now in urgent need of identifying the best pedagogical approaches to foster this abrupt change in teaching platform. This study investigated how English as a foreign language (EFL) teachers acquired information and communication technology (ICT) literacy for online class delivery. Using a qualitative inquiry, the study employed an in-depth interview to gather data from three Thai EFL university teachers from three different north-eastern government universities in Thailand. The thematic analysis revealed that the acquisition of ICT literacy included three stages – before, during, and post-online teaching. Specifically, EFL teachers acquired ICT literacy through self-exposure to existing tutorials, peer-to-peer learning, student-to-teacher collaboration, ongoing teaching practice, expert-to-teacher learning, and engagement in formal workshops. EFL teachers also raised the issue of confidence in using technology and future integration of technology in a classroom-based paradigm. Pedagogical implications for other contexts encountering similar challenges are also discussed.